THE EFFECTIVENESS OF CITRONELLA OIL WITH 100% CONCETRATION AS BASIC COMPOUND OF ELECTRIC MOSQUITO LIQUID VAPORIZER AGAINTS Culex quinquefasciatus ADULT MOSQUITOES - , CHRISTY RUDITA RIVANTI; , dr. Tri Baskoro Tunggul Satoto, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: To prevent further increment of filariasis incidence, vector control method is needed. One of the most common methods is electric liquid vaporizer. Citronella oil 100% (Cymbopogon nardus) which are less toxic to humans and less resistance producing to mosquitoes,are preferred. Objective : To find out the insecticidal ability of Citronella oil 100% (Cymbopogon nardus) as the basic compound of electric liquid mosquito vaporizer against Culex quinquefasciatus adult mosquitoes. Methods: The research subjects were 300 Culex quinquefasciatus mosquitoes, aged 2-5 days. Subjects were divided into 3 groups: group A (negative control), group B (Citronella oil),and group C (positive control). Twenty-five mosquitoes were put in a 18m3 room previously exposed with electric liquid vaporizer. Knockdown time (KT1, KT50, KT95, KT100) and 24-hours mortality were observed. Replication test were done 3 times. Result :KT is not found in group A. In Group B, the KT1 is 90 minutes 21 seconds. Group C KT1 is 11 minutes 65 seconds, KT50 mean is 46 minutes 51 seconds, KT95 is 95 Minutes 58 seconds and KT100 is 108 minutes 45 seconds. With the mortality rate mean of Group A, B and C are 0%, 32% and 93.33% respectively. Conclusion: Citronella oil(Cymbopogon nardus) has killing ability but not effective against Culex quinquefasciatus.